Meningkatkan Kemampuan Berpikir Kritis pada PAKBP dengan Model PBL Berbantuan Media Audio-Visual Materi Allah Membimbing Umat Israel Fase B SDN 071096 Mandrehe - Barnabas Berkat Gulo (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
This study aims to improve students' critical thinking skills in Catholic Religious Education through the implementation of Project-Based Learning (PBL) models assisted by audio-visual media. The focus of this research is the material "God Leads the People of Israel" for Phase B at SDN 071096 Mandrehe. PBL was chosen for its ability to build 21st-century skills such as critical thinking, collaboration, and communication, as stated by Bell (2010). Audio-visual media was used to facilitate students' understanding of the historical and theological context of the material, supporting Mayer's (2009) assertion that this media helps students construct better knowledge. The research results show a significant improvement in students' critical thinking skills. These findings are expected to serve as a basis for developing teaching methods in religious education.